Patient engagement and shared decision-making in trial recruitment intervention studies: a systematic review - Morgan, Tamara L.; Hudek, Natasha; Carroll, Kelly; Yee, Mei-Lin; Inglis, Juliette; Fergusson, Dean A.; Gillies, Katie; Richards, Dawn P.; Semchishen, Seana N.; Presseau, Justin; Grimshaw, Jeremy; Graham, Ian D.; et al. (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Supporting participation decisions and experiences in clinical trials is a persistent challenge that could be improved by two areas: patient engagement (PE), which involves actively collaborating with patients to enhance research relevance and value, and shared decision-making (SDM), which involves helping individuals make evidence-informed, values-based decisions about participation. The extent to which PE and SDM have informed trial recruitment interventions has not been synthesized. Objectives We aimed to explore (1) how PE informed recruitment interventions, both in general and among equity-deserving populations, and whether demographic differences existed between studies using and not using PE, and (2) how SDM has informed recruitment interventions, both in general and among equity-deserving populations. Methods We identified randomized and quasi-randomized recruitment intervention studies from a prior Cochrane review and the Online Resource for Research in Clinical triAls database. We assessed recruitment interventions for reporting of PE and coded the level at which PE occurred (‘substantive engagement’, ‘limited engagement’, ‘both’, ‘unclear’, or ‘no engagement’) and the areas in which PE occurred (development of the research question, intervention design, selecting outcomes, dissemination/implementation, or ‘other’). We coded SDM across six domains: providing information about options, probabilities, clarifying outcomes, guidance in deliberation, using evidence, and disclosure and transparency. Results Of the 122 recruitment intervention studies included, 37 (30.3%) reported PE, although limited engagement was most common (n = 22; 59.5%). PE was most often used in designing the recruitment intervention (n = 32; 86.5%) followed by ‘other’ (n = 11; 29.7%; e.g., PE supporting participant recruitment efforts), developing the research question (n = 2; 5.4%), selecting outcomes (n = 3; 8.1%), and dissemination/implementation (n = 3; 8.1%). SDM was occasionally reported (n = 25; 20.5%), most commonly as ‘providing information about options’ (n = 11; 9.0%). Equity-deserving populations were the focus of 24 studies (19.7%); 11 of these also used PE (9.0%). Conclusions Efforts to improve trial participation have not been informed by literature around patient lived experiences. Recruitment interventions infrequently reported any PE and occasionally mentioned SDM. When PE was mentioned, it was usually limited. These results hold among studies involving equity-deserving populations. Greater consideration of PE and SDM could enhance trial recruitment, research impact, trial participation experiences, and equity in trial recruitment.

Plain English abstract Background Getting people to participate in clinical trials is challenging. Two approaches that can help are working closely with patients to ensure the research is important to them (called patient engagement, or PE) and helping them understand their options to make informed choices about whether to participate (called shared decision-making, or SDM). Objectives We wanted to find out how PE and SDM are used when recruiting people for trials in general and when recruiting populations that are often left out of trials. We also wanted to find out the differences between studies that use PE and those that do not. Methods We reviewed studies about how people are recruited into trials. We checked whether these studies used PE, how engaged patients were (ranging from very engaged to not engaged at all), and where they were engaged, such as helping to choose the research question or sharing results. We also reviewed how SDM was used, such as providing information about options or using evidence to help people decide. Results Of 122 studies, only 37 mentioned PE, mostly at low levels of engagement. PE was mostly used to help design the recruitment strategy. Only 25 studies mentioned SDM, mainly by providing people with information. Only 24 studies focused on groups that are often overlooked, and only 11 of these used PE. Conclusions Most efforts to ask people to join trials have not reflected patients’ real-life experiences. Using PE and SDM more effectively could help more people participate and lead to fairer recruitment.